2012
DOI: 10.1159/000339303
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pathways in the Pathobiology of Human Abdominal Aortic Aneurysms

Abstract: Objectives: Abdominal aortic aneurysm (AAA), a dilatation of the infrarenal aorta, typically affects males >65 years. The pathobiological mechanisms of human AAA are poorly understood. The goal of this study was to identify novel pathways involved in the development of AAAs. Methods: A custom-designed ‘AAA-chip’ was used to assay 43 of the differentially expressed genes identified in a previously published microarray study between AAA (n = 15) and control (n = 15) infrarenal abdominal aorta. Protein analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 79 publications
5
60
0
Order By: Relevance
“…Other studies have investigated cultured AAA cells from human patients. 8 The secretome, proteome, or transcriptome might also be good targets for identifying biomarkers, either from whole-aorta tissue [9][10][11][12][13] or from the AAA-separated layers. 14,15 However, because AAA is a complex disease, and aneurysmal tissue is similarly complex, proteomic analyses of whole-organ AAA tissue can hide cell-specific targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have investigated cultured AAA cells from human patients. 8 The secretome, proteome, or transcriptome might also be good targets for identifying biomarkers, either from whole-aorta tissue [9][10][11][12][13] or from the AAA-separated layers. 14,15 However, because AAA is a complex disease, and aneurysmal tissue is similarly complex, proteomic analyses of whole-organ AAA tissue can hide cell-specific targets.…”
mentioning
confidence: 99%
“…25 Two independent groups using proteomic analysis have discovered that peroxiredoxin-1 (PRDX-1) might be a biomarker for AAA. 8,12 More precisely, Lamblin et al 8 showed that PRDX-1 is expressed by monocyte-derived macrophages. Studying the 2 macrophage subtypes in human AAA might, therefore, improve our understanding of their role in this disease and help to identify potential biomarkers secreted by these cells into the blood circulation.…”
mentioning
confidence: 99%
“…ADAMs 8, 9, 10, 12, 15 and 17 were found to be expressed in both AAA and control aorta [19], and ADAM17 (TACE) was upregulated in human AAA aortic specimens and was associated with chronic inflammation, increased neoangiogenesis and ECM disruption [9]. The role that ADAM17 plays in the inflammation and proteolytic degradation of ECM in the vessel wall markedly contributes to the formation and rupture of an AAA [5,6]. ADAM17 is capable of cleaving several other cell surface molecules, such as TNF-α, TNFR1 and TNFR2, as well as IL-6R and IL-1RII, which are considered to be involved in inflammatory processes of the vasculature [10].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple characteristics of AAA pathogenesis involve chronic inflammation [2], autoimmunity, increased neoangiogenesis [3], enhanced oxidative stress [4], and degradation of the extracellular matrix (ECM) [5]; however, the precise mechanisms of AAA formation and progression remain elusive [6]. …”
Section: Introductionmentioning
confidence: 99%
“…AA are char-acterised by the medial degeneration, and investigations of the pathogenesis of AA focus mainly on the effects of hypertension, age, and apoptotic pathway activation, which finally results in the apoptosis of smooth muscle cells and degradation of the extracellular matrix [11,15]. Hinterseher et al [4] showed that gene such as GATM, FOSB, ADCY7 and proteins such as CXCR4, PLEK, and GATM participated in the development of AA using a custom-designed "AA-chip", Western blot and immunohistochemical staining. However, the precise underlying aetiology of AA remains unclear.…”
Section: Introductionmentioning
confidence: 99%